Geochemical characteristics of major and minor elements of soil and rocks in Sør Rondane Mountains, East Antarctica - Noriyoshi, Tsuchiya; Hideki, Miura; Yusuke, Suganuma; Fumio, Hashizume; Shin-ichi, Yamasaki; Ryoichi, Yamada; Yasumasa, Ogawa; Satish, Kumar; Tetsuo, Kawakami; Masahiro, Ishikawa; Geoff, Granthan (2010)
第30回極域地学シンポジウム「極域から探る固体地球ダイナミクス」 12月2日（木） 国語研究所 ２階講堂 conference object